Base Case Simulation of a Semi-Batch Emulsion Copolymerization Process - Iwan Harsono; Herman Hindarso; Nani Indraswati (ASEAN Journal of Chemical Engineering, 2006)
It has been long recognized that emulsion polymerization is a complex heterogeneous process involving transport of monomers and other species and free radicals between aqueous phase and organic phases. Though there are a number of models available in the literature, most of them deal only with specific aspects in emulsion polymerization and are far from being general. To simulate this complicated process and to achieve an adequate level of understanding, a Polymer Plus' software from Aspen Technology, Inc. has been used. The objective of this work is to illustrate the principle use of Polymers Plus' and to simulate and analysis the free-radical seeded emulsion copolymerization of styrene-butadiene process model in a semi-batch reactor. The base case simulation can be used to gain process understanding by analyzing how process variables and operating conditions during the course of a semi-batch reactor affect product quality.